Dose rate in the highest irradiation area of the rectum correlates with late rectal complications in patients treated with high-dose-rate computed tomography-based image-guided brachytherapy for cervical cancer. (19th April 2021) - Isohashi, Fumiaki; Akino, Yuichi; Matsumoto, Yuri; Suzuki, Osamu; Seo, Yuji; Tamari, Keisuke; Sumida, Iori; Sawada, Kenjiro; Ueda, Yutaka; Kobayashi, Eiji; Tomimatsu, Takuji; Nakanishi, Erina; et al.
Abstract: The purpose of this study was to evaluate the effect of dose rate to the rectum on late rectal complications in patients treated with computed tomography (CT)-based image-guided brachytherapy (IGBT) for cervical cancer. The subjects were 142 patients with cervical cancer who underwent Ir-192 high-dose-rate (HDR)-IGBT between March 2012 and January 2018. The dose rate to the rectum was calculated using in-house software. The minimum, mean and maximum effective dose rate (EDR) was calculated for voxels of the rectal volume covered by cumulative doses >D0.1cc, >D2cc, and > D5cc . The average EDR of three to four brachytherapy sessions was calculated (EDR for patients; EDRp ). The total dose of the rectum was calculated as the biologically equivalent dose in 2-Gy fractions (EQD2 ). The associations between EDRp for D0.1cc, D2cc, and D5cc and the respective rectal EQD2 values with late rectal complications were then analyzed. The median follow-up period was 40 months. Patients with rectal complications of ≥Grade 1 received a significantly higher mean EDRp for D0.1cc–5cc and had a greater EQD2 for D0.1cc–5cc . Multivariate analysis was performed using the mean EDRp for D2cc, EQD2 for D2cc, heavy smoking and BMI. Of these four variables, mean EDRp for D2cc (HR = 3.38, p = 0.004) and EQD2 for D2cc (HR = 2.59, p = 0.045) emerged as independent predictors for late rectal complications. In conclusion, mean EDRp and EQD2 were associated with late rectal complications in patients treated with HDR CT-based IGBT for cervical cancer.